Electronic criminal vetting and management system (eCVMS) - Sibanda, Wellington (Midlands State University, 2018)
The purpose of this research was to provide a working and lasting solution to the challenges being faced by the Zimbabwe Republic Police (ZRP) at Criminal Investigations Department (CID), Central Criminal Bureau (CCB) in particular. To achieve the best results for this project, a number of methodologies, information gathering techniques and development tools were carefully used. The researcher used Interviews, Observations and Questionnaires to gather data from the users/CID officers at CCB. The information was collected on how the current system operates, challenges they are facing and what they suggest could be done to better the current system. The tools which were used to develop the Electronic Criminal Vetting and Management System include Visual Studio 2012, SQL Server 2012(relational database) , Microsoft 2010 (documentation). The electronic Criminal Vetting and Management System (eCVMS) is an application that focuses on the activities of police officers in their dealings with criminal elements within Zimbabwe. It tracks criminal history of all convicted persons within the country from the time they are arrested a local police station, prosecuted and convicted at our local courts. The system will ignore petty offences that are dealt with by way of fines at police stations such as minor traffic offences and other miscellaneous offences. The system will electronically issue Police Clearance certificates to individual clients referred by various organisations seeking their (clients) criminal record. It will also supply management at police establishments and courts with vital criminal information needed for decision making.